PENGARUH NPK ORGANIK DAN BIOSAKA TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG KEDELAI (Glycine max (L) Merr.) VARIETAS WILIS - Ranti Manullang; Fathurrahman (UIR Press, 2025)
This study aimed to determine the interaction and main effects of organic NPK fertilizer and biosaka on the growth and yield of soybean (Glycine max (L.) Merr.) cultivar Wilis. The research was conducted at the Experimental Farm of the Faculty of Agriculture, Universitas Islam Riau, from November 2024 to January 2025 using a factorial Completely Randomized Design (CRD) with two factors. The first factor was the dose of organic NPK fertilizer (0, 20, 40, and 60 g per plant), while the second factor was the concentration of biosaka (0, 2, 4, 6, and 8 ml L⁻¹ of water). The observed parameters included plant height, stem diameter, flowering time, harvesting time, leaf chlorophyll content, number of active root nodules, number of pods per plant, fresh seed weight per plant, dry seed weight per plant, and 100-seed dry weight. Data were statistically analyzed and further tested using the Honestly Significant Difference (HSD) test at the 5% level. The results showed that the interaction between organic NPK fertilizer and biosaka significantly affected stem diameter, flowering time, leaf chlorophyll content, number of active root nodules, number of pods per plant, fresh seed weight per plant, dry seed weight per plant, and 100-seed dry weight but had no significant effect on plant height and harvesting time. The best treatment was obtained with 60 g of organic NPK fertilizer per plant combined with 8 ml L⁻¹ biosaka. The main effect of organic NPK fertilizer significantly influenced all observed parameters, with the best result at a dose of 60 g per plant. Similarly, biosaka had a significant impact on all observed parameters, with the best result at a concentration of 8 ml L⁻¹.